2020
DOI: 10.1177/1056492620982375
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal View on the Academic–Practitioner Gap

Abstract: There is consensus about the existence of an academic–practitioner gap in management studies. However, views diverge about the width of the gap and the possibility to bridge it. By introducing diffusion theory into the debate, this article shows the gap is not static, but widens or closes over time. We reconceptualize the academic–practitioner gap as consisting of two different diffusion cycles, one in practice and one in academia. Depending on the shape and timing of these cycles, the academic–practitioner ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 163 publications
(306 reference statements)
0
7
0
Order By: Relevance
“…The fact that both discourse communities contribute synchronously to the growth and decline of fads also suggests that the often-proclaimed academic-practitioner gap (Birkinshaw et al, 2016;Deadrick and Gibson, 2007;Perea and Brady, 2017;de Man et al, 2021) does not seem to exist for these fads. Even though both communities address the same fads, often to an equal extent, they do so according to their own terms with variations in peaks, intensity, and endurance of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that both discourse communities contribute synchronously to the growth and decline of fads also suggests that the often-proclaimed academic-practitioner gap (Birkinshaw et al, 2016;Deadrick and Gibson, 2007;Perea and Brady, 2017;de Man et al, 2021) does not seem to exist for these fads. Even though both communities address the same fads, often to an equal extent, they do so according to their own terms with variations in peaks, intensity, and endurance of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, popularization has been viewed as the one-way transfer of knowledge from academia to the practitioner domain. Scholars adopting this view have suggested an academic-practitioner gap in the management field, because scholarly research published in peer-reviewed journals is rarely taken up by practitioner magazines or generally not relevant for practitioners (Baldridge et al, 2004;Bansal et al, 2012;Bartunek and Rynes, 2014;Wastell, 2014;Adler, 2016;Perea and Brady, 2017;de Man et al, 2021). The practitioner community, meanwhile, develops its own management techniques with little need for scholarly input, which entails that knowledge about the effective management of organizations is understood as being created in two loosely connected domains that are mostly self-referential (Tranfield and Starkey, 1998;Kieser and Leiner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the accessibility of research contributions to practitioners constitutes another barrier between research and practice (Tucker, 2013;Tucker and Lowe, 2014;Tucker and Parker, 2014;Tucker and Schaltegger, 2016). Last but not least, institutional (Tuttle and Dillard, 2007) as well as time-related aspects, including different time horizons (Inanga and Schneider, 2005;Grosu et al, 2015;de Man et al, 2020;Ratzinger-Sakel and Gray, 2015) or a time lag between research and practice (Bartunek and Rynes, 2014), help to explain the research-practice gap.…”
Section: Systematization Of the Research-practice Gapmentioning
confidence: 99%
“…Last but not least, institutional (Tuttle and Dillard, 2007) as well as time-related aspects, including different time horizons (Inanga and Schneider, 2005; Grosu et al. , 2015; de Man et al. , 2020; Ratzinger-Sakel and Gray, 2015) or a time lag between research and practice (Bartunek and Rynes, 2014), help to explain the research-practice gap.…”
Section: Theoretical Background Of the Research-practice Gap In Accou...mentioning
confidence: 99%
“…It is often observed that the complexity and pace of contemporary business operations often creates a knee-jerk business decision culture, with continual guesswork as to what works and where to prioritize resources (Rousseau and Barends, 2011). Not unlike other disciplines and departments (de Man et al ., 2020; Jex, 2002), managers of HR functions often make uninformed (other than from their own experiences) critical choices affecting the future of their firms, their employees and the public (Crespin-Mazet and Ingemansson-Havenvid, 2021; Rousseau and Barends, 2011), often neglecting opportunities to investigate their business challenges via academic inquiry (Rousseau and Barends, 2011; Subramony, 2006; Vosburgh, 2022).…”
Section: Introductionmentioning
confidence: 99%